Exploring the relationships between personality and color preferences - Jue, Juliet; Ha, Jung Hee (Frontiers in Psychology, 2022)
This study set out to quantitatively examine the relationship between personality and color, focusing on connotations and preference. A total of 854 Koreans, aged from 20 to 60, participated in the study. They indicated which colors they associated with various personality words, completed the Ten Item Personality Inventory, and ranked their color preferences. We analyzed the data using frequency analysis, correlation analysis, t-tests, regression analysis, and cluster analysis. The analyses revealed that all five personality types have characteristic color associations. Through regression analysis, we found that color preference can significantly predict personality. The comparison among personality groups produced by cluster analysis confirmed that people with strong specific personalities prefer the colors that symbolize their personalities. This study’s findings highlight the relationship between personality and color preference. The limitations and suggestions for future studies are also presented.